Voltage regulation of dual stator permanent magnet synchronous generator - Gupta S.K.; Srivastava R.K.; Mahendra S.N. (My University, 2025)
The paper discusses the feasibility studies of a dual stator permanent magnet synchronous generator in stand-alone renewable energy generation. In wind power, fresh water or sewage water stream based power generation, the turbine is driven at variable speed causing either over voltage or under voltage. The paper utilizes the principle of induction regulation for voltage control. FEM analysis has been reported for the generator using ANSYS Multiphysics for magnetic analysis. The use of induction regulation in controlling voltage dynamics of proposed machine for different rotor speed has been proposed, discussed and justified by simulation result. © 2015 IEEE.